Devising a mathematical model for pattern-based enterprise data integration - Галушка, Илона Николаевна; Щербак, Сергей Сергеевич (Eastern-European Journal of Enterprise Technologies, 2015)
The paper considers the problem of centralized automation policy at domestic enterprises that leads to a decreasing quality of subdivision interaction and productivity of an enterprise operation. To solve such problems, we have suggested an approach based on collective use of the concept of combined data and the enterprise service bus. The devised classification of the existing patterns of corporative data integration and brief characteristics of integration platforms IBM WebSphere, TransparentGateways, and OpenLinkVirtuoso have secured an adequate decision for integration аt the data level in favor of adaptable, easily customizable, and intuitive integration tools. We have suggested a mathematical model for the specialized integration system of corporative data as part of the enterprise service bus. The model provides logical consistency and formal description for the structures of integrated data as patterns for hierarchically arranged distributed objects with unified access interfaces. The model contains mapping functions that formally describe integration processes on the basis of related data and object-oriented approach. This allows increasing the interaction productivity for inherited enterprise information systems at the expense of integration patterns. We have considered practical aspects of corporative data integration that demonstrate advantages and efficiency of decisions based on the suggested model, the selected integration platform OpenLinkVirtuoso, and the SPARQL protocol. The devised architecture of the specialized system for integrating corporative data is based on the enterprise service bus and related data technologies. The architecture means a complex of integration brokers and describes, in terms of related data concepts, the relay of the integrated message between the sources of inherited information systems.